An Unmatched Radio Frequency Chain for Low-Field Magnetic Resonance Imaging - Harper, Joshua R.; Zárate, Cristhian; Krauch, Federico; Muhumuza, Ivan; Molina, Jorge; Obungoloch, Johnes; Schiff, Steven J. (Frontiers in Physics, 2022)
Magnetic Resonance Imaging (MRI) is a safe and versatile diagnostic tool for intracranial imaging, however it is also one of the most expensive and specialized making it scarce in low to middle income countries (LMIC). The affordability and portability of low-field MRI offers the potential for increased access to brain imaging for diseases like Hydrocephalus in LMIC. In this tutorial style work, we show the design of a low powered and low cost radio-frequency chain of electronics to be paired with a previously reported prepolarized low-field MRI for childhood hydrocephalus imaging in sub-Saharan Africa where the incidence of this condition is high. Since the Larmor frequency for this system is as low as 180 kHz, we are able to minimize the impedance of the transmit coil to 5 ohms rather than match to 50 ohms as is traditionally the case. This reduces transmit power consumption by a factor of 10. We also show the use of inexpensive and commonly available animal enclosure fencing (‘chicken wire’) as a shield material at this frequency and compare to more traditional shield designs. These preliminary results show that highly portable and affordable low-field MRI systems could provide image resolution and signal-to-noise sufficient for planning hydrocephalus treatment in areas of the world with substantial resource limitations. Employment of these technologies in sub-Saharan Africa offers a cost-effective, sustainable approach to neurological diagnosis and treatment planning in this disease burdened region.